Investments an introduction - Mayo, Herbert B. (Cengage Learning, 2017)
Gain a full understanding of today's most important investment topics from the perspective of an individual financial planner with Mayo's INVESTMENTS: AN INTRODUCTION, 13E. This inviting approach introduces the process of investing and the many alternatives available for constructing a strong investment portfolio. You master the investing fundamentals needed for success on the CFP® exam while developing more advanced investing skills. You learn to manage your assets as an active portfolio manager or simply as an informed investor. This edition highlights how to make solid investment decisions with an overview of today's most pertinent investment opportunities and challenges. Updates highlight the latest changes in taxation and investment planning prompted by the 2018 Tax Cuts and Jobs Act (TCJA). An ongoing Financial Advisor's Investment Case and expanded coverage of stock valuation ratios, stock repurchases, and dividend payments emphasize how to apply what you've learned to daily decisions.